Colonising concepts of the good citizen, law's deceptions, and the treaty of Waitangi - Nan Seuffert (Law Text Culture, 1998)
The dominant story of the founding of New Zealand is a simple one of cession of sovereignty by the indigenous Maori people to the British in the Treaty of Waitangi 1840. One notable aspect of the dominant legal portrayals of the Treaty signing, and subsequent legal cases, is their repression of the glaring discrepancies between the Maori version of the Treaty, signed by most Maori leaders, and the English versions. Historical arguments suggest that this discrepancy is the result ofdeliberate deceptio.n on the part of British missionaries translating the Treaty into Maori (Walker 1990: 9L Walker 1989: 269, Ross 1972: 20, Ross 1972 NZ]H: 140-141). I argue that this act ofdeception was necessary to the colonisation of New Zealand, and to the formation of New Zealand as a unified nation-state. The deceptive, or 'appropriative' mistranslation (Constable 1996: 634635), of the Treatywas the performance of an ideal of the forwardgazing (white, male) citizen who has successfully shed his history (Davidson 1997: 19, Bernal 1994: 125-127); it served both the individual interests of the citizen/subject translator and the interests of nation-building.